The Twelve Tribes of Hattie - Mathis, Ayana (New York : Alfred A. Knopf, 2012)
Traces the story of Great Migration-era mother Hattie Shepherd, who in spite of poverty and a dysfunctional husband uses love and Southern remedies to raise nine children and prepare them for the realities of a harsh world.
Keywords: African American women -- Fiction; African Americans -- Fiction -- Philadelphia (Pa.); Family life -- Fiction; Historical fiction